Alcohol Abuse - Zima, Tomáš (EJIFCC, 2018)
Chronic alcohol consumption is a world-wide socioeconomic problem. Three metabolic pathways of ethanol were describe in human - alcohol dehydrogenase (ADH), microsomal ethanol oxidizing system (MEOS, CYP2E1) and catalase. Ethanol directly bounds to different molecules (e.g. etylglucuronid) and ethanol per se and its metabolites have toxic effect on biological stuctures. Alcohol abuse is well known for its liver diseases e.g. cirrhosis (the most frequent cause in Europe and US) and hepatocellular carcinoma. Chronic alcohol comsumption leads to cardiovascular diseases (e.g. hypertension, cardiomyopathy), pancreas damage, myopathies, osteoporosis, neurological and psychiatry diseases including fetal alcohol syndrome and addiction. Alcohol consumption may lead to cancer via several mechanisms, per se (solvent for carcinogens) and its metabolites. Acetaldehyde, a cancerogen, has mutagenic effect on DNA, oxidation of ethanol produces the reactive oxygen and nitrogen species with different effects e.g. cell transformation, DNA, protein and lipid damage. The changes of folate metabolism, altered methylation of DNA, reduction of retionic acid influences on cancer development. The high rate of alcohol consumption has become a great social-health problem. Consumption of alcohol is still increasing in many countries, but in some countries is stable or decreasing (e.g. Mediterranean region). The data across Europe shows that 10% of all cancers in men and 3% of all cancers in women can be attributed to alcohol consumption. Australian data suggests that alcohol intake accounts for 5% of the total cancer burden of disease. Alcohol consumption is one of the leading causes of mortality and morbidity in many developed countries.
Keywords: cancer; alcohol dehydrogenase; epidemiology; liver diseases; alcohol